2011
DOI: 10.1159/000327566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of One-Year Subcutaneous and Sublingual Immunotherapy on Clinical and Laboratory Parameters in Children with Rhinitis and Asthma: A Randomized, Placebo-Controlled, Double-Blind, Double-Dummy Study

Abstract: Background: It has been reported that both sublingual (SLIT) and subcutaneous (SCIT) allergen-specific immunotherapy have clinical efficacy, yet there are rather few comparative placebo studies of children. We aimed to investigate the clinical and immunological efficacy of mite-specific SLIT and SCIT versus a placebo in rhinitis and asthma in children. Methods: The outcomes of this 1-year, randomized, placebo-controlled, double-blind, double-dummy study were symptom and medication scores, visual analog scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
131
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(149 citation statements)
references
References 81 publications
9
131
0
9
Order By: Relevance
“…Desiree et al [16] have assessed the findings from 31 studies on SCIT and concluded that the patients treated with D. pteronyssimus extract experienced 12-fold reduction in specific BHR after only 4-month of treatment compared with no change in the control group (p=0.002). Similar results were obtained in a study by Yukselen et al [17], which included 10 children treated with SCIT, 10 with SLIT and 10 children were on placebo during one year. The patients treated with SCIT showed significant increase in HDM (house dust mite) -specific bronchial provocation doses after 12 months.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Desiree et al [16] have assessed the findings from 31 studies on SCIT and concluded that the patients treated with D. pteronyssimus extract experienced 12-fold reduction in specific BHR after only 4-month of treatment compared with no change in the control group (p=0.002). Similar results were obtained in a study by Yukselen et al [17], which included 10 children treated with SCIT, 10 with SLIT and 10 children were on placebo during one year. The patients treated with SCIT showed significant increase in HDM (house dust mite) -specific bronchial provocation doses after 12 months.…”
Section: Discussionsupporting
confidence: 87%
“…Mean FEV1 values in their study showed an average increase by 6.3% in SCIT, 5.5% in SLIT and 0.7% in the placebo group. When compared with baseline values, FEV1 increased significantly in SCIT and SLIT, but did not change significantly in the placebo group [17].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Em estudos clínicos, além de servir como fator de identificação a sensibilizações, serve como avaliação da resposta a tratamentos para atopia, como, por exemplo, a imunoterapia [30] e em programas de educação em doenças alérgicas, fazendo com que o paciente visualize a resposta alérgica, reforçando a informação verbal e ajudando na avaliação da causa-efeito da alergia. Medidas de controle ambiental devem ser mantidas em conjunto com a prevenção da sensibilização alérgica e na redução de manifestações clínicas em pacientes com asma ou rinite alérgica [32].…”
Section: /10unclassified
“…Alternative routes Sublingual -Sublingual administration of allergen-containing drops or tablets [17,24,[74][75][76][77][78][79] Oral -Oral administration of allergens (i.e. allergy vaccines that are swallowed) [68][69][70] Intralymphatic -Injection of allergy vaccines into the lymph node (instead of subcutaneous injection) [81][82][83] Epicutaneous -Epicutaneous administration of allergens using patch application [84][85][86][87] C. Virus-like particles…”
Section: Coupled Allergensmentioning
confidence: 99%